Habitus Creativity of Elementary Teacher Education Department Students in Creating "Batik Cap" - Probosiwi Probosiwi (IJCAS (International Journal of Creative and Arts Studies), 2019)
ABSTRACTThe purposes of this research are finding out the behaviour and creativity patterns of students in making “batik cap”. Subjects of this research were students of the Primary School Teacher Education Department at Universitas Ahmad Dahlan Yogyakarta who took the Art and Skills Education course in the even semester of the Academic Year 2018/2019. The stages of the process analyzed include making batik designs, creating “batik cap” masters, “batik cap” artworks, and finishing the artworks. The research method is qualitative research. Data collection techniques are done by interview, observation, and document review. The data analysis technique used is narration. The results showed that 4P concept contains habitus as a system of practical production schemes, systems of perception, and appreciation practically related to aesthetics that allow for non-aesthetic responses within an object, differently defined in terms of philosophical logic. Students did the practices they had followed the procedure of creative thinking quite well. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pola perilaku dan kreativitas siswa dalam pembuatan “batik cap”. Subjek penelitian ini adalah mahasiswa Program Studi Pendidikan Guru Sekolah Dasar di Universitas Ahmad Dahlan Yogyakarta yang mengambil mata kuliah Pendidikan Seni dan Keterampilan pada Semester Genap Tahun Akademik 2018/2019. Tahapan proses yang dianalisis meliputi pembuatan desain, master "batik cap", karya seni "batik cap", dan menyelesaikan karya seni. Metode penelitian adalah kualitatif. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan tinjauan dokumen. Teknik analisis data yang digunakan adalah narasi. Hasil penelitian menunjukkan bahwa konsep 4P berisi habitus sebagai sistem skema produksi praktis, sistem persepsi, dan penghargaan yang secara praktis terkait dengan estetika yang memungkinkan respons non-estetika dalam suatu objek, berbeda didefinisikan dalam hal logika filosofis. Mahasiswa melakukan praktik cukup baik dengan mengikuti prosedur berpikir kreatif.